Word-Formation Models of Bone and Joint Nomenclature in the Medical Terminological System (Eurasian Journal of Philology Science and Education, 2025)
This article investigates the word-formation models underlying Kazakhized bone-and-joint terms within the medical terminological system. The study is motivated by a persistent tension between, on the one hand, medicine as a domain characterized by internationally standardized classifications and nomenclatures, and, on the other, the need for national-language adaptation that secures conceptual precision, linguocultural coherence, and stable usage across educational and clinical communication. The material is drawn from a multi-layered set of sources, including internationally codified bone-and-joint designations, officially approved national terminological variants, lexicographic records in Kazakh medical dictionaries, and evidence from real usage in teaching materials and clinical texts. The main aim is to identify formation patterns of Kazakhized terms related to the musculoskeletal system and to systematize them through a structural typology of word-formation models. The analysis demonstrates that analytic patterns are highly productive: multi-component constructions (modifier + head), as well as numeric-hierarchical and locative specifications, provide increased informational density and support medical exactness by encoding anatomical relations directly in the term. Calque-based formations contribute to cross-border recognizability by preserving the semantic-structural “skeleton” of international terms, yet they may generate challenges for linguistic naturalness and internal standardization. Synthetic (affixational) formations appear comparatively limited in this segment, whereas hybrid structures combining international components with Kazakh morphological or lexical elements reveal the transitional nature of current Kazakhization practices. The article also highlights discrepancies between normative sources and actual usage, resulting in parallel variants. The findings can support applied tasks of codification, lexicography, standardizing educational and clinical documentation, and enriching digital terminological resources.Keywords: national terminology, medical terminological system, Kazakhization processes, word-formation models, bone and joint terms.